C0-CULTURE OF AMYLOLYTIC FUNGI Aspergillus niger AND OLEAGINOUS YEAST Candida orthopsilosis ON CASSAVA WASTE FOR LIPID ACCUMULATION - Atit Kanti; I Made Sudiana (Research Center for Biology-Indonesian Institute of Sciences, 2017)
The objective of study was to evaluate the effectiveness of co-culture between amylolytic fungi Aspergillus niger and lipid accumulating yeast Candida orthopsilosis for lipid accumulation on cassava waste. When grown in 5 % starch medium, all microbes was able to grow, but best growth was observed on Aspergillus niger, other microbes grew slower. Moderate growth was observed on Saccharomycopsis fibuliger. The two isolates were then selected for further studies. Aspergillus niger and Saccharomycopsis fibuliger were amylolytic microbes. The amylolytic activities were affected by temperature, pH and nitrogen sources. Optimum temperature and pH for enzyme production were 30°C and 7.0 respectively. Both yeast extract and sodium nitrate were good nitrogen sources for amylase production. On cassava waste, the highest biomass and total lipid content were obtained by co-culture of Aspergillus niger and lipid accumulating yeast Candida orthopsilosis. Major lipid composition was oleic acids and strearic acids. The ability of co-culture of Aspergillus niger and lipid accumulating yeast Candida orthopsilosis grew and accumulated lipid on cassava waste would suggest that these culture were candidate for biofuel production.